Evolution of Ag nanostructures created from thin films: UV–vis absorption and its theoretical predictions - Kozioł, Robert; Łapiński, Marcin; Syty, Paweł; Koszelow, Damian; Sadowski, Wojciech; Sienkiewicz, Józef E.; Kościelska, Barbara (Beilstein Journal of Nanotechnology, 2020)
Ag-based plasmonic nanostructures were manufactured by thermal annealing of thin metallic films. Structure and morphology were studied using scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HR-TEM) and X-ray photoelectron spectroscopy (XPS). SEM images show that the formation of nanostructures is influenced by the initial layer thickness as well as the temperature and the time of annealing. The Ag 3d and Ag 4d XPS spectra are characteristic of nanostructures. The quality of the nanostructures, in terms of their use as plasmonic platforms, is reflected in the UV–vis absorption spectra. The absorption spectrum is dominated by a maximum in the range of 450–500 nm associated with the plasmon resonance. As the initial layer thickness increases, an additional peak appears around 350 nm, which probably corresponds to the quadrupole resonance. For calculations leading to a better illustration of absorption, scattering and overall absorption of light in Ag nanoparticles, the Mie theory is employed. Absorbance and the distribution of the electromagnetic field around the nanostructures are calculated by finite-difference time-domain (FDTD) simulations. For calculations a novel approach based on modelling the whole sample with a realistic shape of the nanoparticles, instead of full spheres, was used. This led to a very good agreement with the experiment.
Keywords: dewetting; finite-difference time-domain (FDTD) method; plasmon resonance; silver (Ag) nanostructures; thin films; UV–vis absorption